Mães encarceradas no Estado de São Paulo, análise a partir dos atendimentos da Defensoria Pública do Estado - Lara, Hellen Pereira (2018)
This research is the result of inquiries relating to the many and cruel improsoned women`s rights violation in the prison system in the state of São Paulo. In order to carry out this study, the capitalist society`s path has been outlined considering this system as a way to underestimate women`s rights in this system. Furthermore, a prison system`s research was carried out in regards to mothers who are imprisoned as well as interviews with experts that work on this field in order to analyze how the Institutional policies in regards to the Public Deffender`s Office named “Mães em Cárcere“ [imprisoned mothers] as well as its performance and challenges. The policies for “Mães em Cárcere” were established in 2011 through dialogues involving Pastoral of Prisoners (Pastoral Carcerária), Land, Work and Citizenship Institute, Public Defender’s Office (Defensoria Pública) among other public institutions that aim at supporting this group. Given the fact that in the state of São Paulo is the place where an increase of criminality levels is observed, the research suggests there is a focus on criminalizing poor suburban work-class layers based on capital. This research finally aims at showing how our society violates these women`s rights leaving ever-lasting wounds in themselves and their families